Didactics: it’s reconstruction from History's Standpoint (Praxis Educativa, 2012)
An inquiry into the historical and social construction of Didactics is made from two hypothetical axes: a - Comenius's foundational conception (XVII c ) appears as an approach which is reductionist (because of being restricted to schooling circles, thus silencing his presentation of education as the axis of a democratic sociopolitical system capable of supporting world peace) and dehistorised (decontextualized from both its political-social-economic environment -amid wars, persecutions, death and poverty- and its pedagogical antecedents the teaching in monasteries, in charge of preserving bodies of knowledge, isolated from society and life, with boarding schools characterized by strict discipline, aimed at selected elites). b - Such treatment strengthens a simplistic notion of education, that has reduced its complexity to merely articulating three elements in the well-known 'didactic triangle'. In this framework of devaluation it is possible to think of Specific Didactics centred on this 'triangle' by which the complex unity of the didactic system is disallowed, without contributing to school improvement. What is possibly left for us to do is re-thinking education m its conceptual complexity, as a system that includes both political ideology and the democratic ideal- the vindication of which for our Latin American peoples is a must.
Keywords: didactics investigation; educational system; method; historical approach; teacher training